Trends in acupuncture for infertility: a scoping review with bibliometric and visual analysis - Tian, Ziyu; Zhang, Chongyang; Liao, Xing; Yang, Sihong; Hong, Yuying; Shi, Anni; Yan, Fei; Pan, Ting; Zhang, Jiajia; Meng, Yan; Robinson, Nicola; Bai, Peng; et al. (Frontiers in Endocrinology, 2024)
Unexplained recurrent implantation failure, and the high cost of assisted reproductive techniques for those experiencing infertility has increasingly resulted in the use of acupuncture. However, the trends and research status of acupuncture on infertility resulted in natural conception have not been systematically summarized. This scoping review and knowledge graph analysis aimed to summarize existing clinical studies on acupuncture for infertility resulted in natural conception.Seven databases including PubMed, Embase, the Cochrane Library, CNKI, VIP, Wan Fang Data and SinoMed were searched up to 1st April 2024. Two authors independently identified related clinical studies and systematic reviews, and extracted data from included studies on acupuncture for infertility. A meta-analysis was conducted based on RCTs, data were synthesized using risk ratios with 95% confidence intervals. Of the 310 articles meeting the inclusion criteria, 274 were primary studies,7 were systematic reviews and 29 were case reports. Reported adverse events included, mild ovarian irritation and early signs of miscarriage. Out of the 274 primary studies, there were 40 (14.60%) cases of male infertility and 234 (85.40%) cases of female infertility. Current research highlights of acupuncture for infertility focused on female infertility caused by polycystic ovary syndrome, ovulation disorder and luteinized unruptured follicle syndrome (LUFS), while acupuncture for male infertility was a hotpot in early research stage. The meta-analysis also suggested that acupuncture was effective than human chorionic gonadotropin (HCG) (RR=1.89, 95%CI (1.47, 2.42),11 RCTs, 662 participants). Acupuncture combined with HCG was comparable to HCG (RR=2.33, 95%CI (1.53, 3.55),4 RCTs,259 participants).Compared with no treatment, acupuncture resulted in higher pregnancy rate (RR=22.12, 95%CI (1.39, 353.09), 1 RCT, 47 participants). There was no statistical difference between acupuncture combined with HCG plus Letrozole and HCG plus Letrozole (RR=1.56, 95%CI (0.84, 2.89),1 RCT, 84 participants).Current research highlights of acupuncture for infertility resulted in natural conception focused on female infertility caused by polycystic ovary syndrome, ovulation disorder and LUFS, while research about male infertility and female infertility caused by block of fallopian tube, thin endometrium and other factors were insufficient. Well-designed confirmatory clinical studies are still needed as the research hypotheses of most studies were unclear.